Results of epizootic monitoring of natural foci of particularly dangerous infections common to humans and animals in Rostov Oblast - E. Y. Lukshina; V. V. Batashev; E. V. Kovalev; G. V. Karpushchenko; V. V. Balakhnova; N. V. Panasyuk; A. A. Alieva; V. V. Sidelnikov; M. M. Schwager; N. V. Polovinka; A. V. Polonsky; F. V. Logvin; et al. (Медицинский вестник Юга России, 2021)
Objective: To analyze the results of epizootic monitoring of natural foci of particularly dangerous infections common to humans and animals in Rostov Oblast to establish their activity.Materials and Methods: The data of epizootic monitoring conducted by zoologists; the results of laboratory research of field material obtained in natural foci of infectious diseases. Descriptive, zoological, genetic, serological methods, and retrospective epidemiological analysis were used.Results: The results of the conducted epizootic monitoring showed the presence in Rostov Oblast of natural foci of particularly dangerous infectious diseases common to humans and animals. While the natural focus of the plague is in a depressed state and does not show activity, in the foci of tularemia, West Nile fever (WNF), Crimean hemorrhagic fever (CHF), ixodic tick-borne borreliosis (ITB), hemorrhagic fever with renal syndrome (HFRS), Q fever, Batai fever, California serogroups, Syndbis revealed the antigens of these pathogens in biological material obtained from small mammals and blood-sucking insects, which indicates the epizootic activity of these foci. In the natural foci of WNF, CHF, ITB, HFRS, cases of these disease among the population were recorded, which confirms the epidemic activity of these foci.Conclusion: The obtained results of epizootic monitoring over the period from 2008 to 2020 emphasize the relevance and necessity of continuing these studies in natural foci in Rostov Oblast.